Peran Anggota Legislatif Dalam Meningkatkan Kesejahteraan Masyarakat Kabupaten Pandeglang - Wiraatmaja, Rafly (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
In Indonesia, the existence of the Regional People’s Representative Council (DPRD) as part of the legislative body plays an important role in strengthening the democratic process at the regional level. The DPRD functions as the people’s representative whose task is to voice the interests of the community in the process of formulating regional policies. This research aims to analyze the role of legislative members in improving the welfare of the people of Pandeglang district. The method used in this research is descriptive qualitative. Data collection carried out in this research was interviews and observations. The research results show that infrastructure development in Pandeglang Regency still needs to be improved so that it is evenly distributed across all sub-districts. With the vast area and diverse community needs, good infrastructure development will support mobility, economic distribution and community welfare, especially in the agricultural and logistics sectors. The regional government and DPRD have an important role in ensuring that development runs effectively and according to targets, so that the plan to improve infrastructure in 2025 is a strategic step to encourage economic growth and prosperity of the Pandeglang community as a whole. The DPRD has an important role as the people’s representative in fighting for the welfare of the people of Pandeglang Regency. Through legislative functions, council members are responsible for ensuring that the policies adopted truly bring benefits to society and pay attention to various existing social problems. Synergy between the DPRD and regional governments is the key to creating policies that are effective and oriented towards people’s welfare. With an evaluation-based approach and good cooperation between the legislature and the executive, it is hoped that development and community welfare in Pandeglang can continue to increase.